The association between longitudinal patterns of adverse childhood experiences, and self-harm and depression in adolescence and early adulthood: findings from the Avon longitudinal study of parents and children. - Farooq, Bushra; Russell, Abigail E.; Allen, Kate; Howe, Laura D.; Mars, Becky (European Child & Adolescent Psychiatry, 2025)
Adverse childhood experiences (ACEs) elevate the risk of self-harm and depression, which are significant public health concerns. This study examined the association between the longitudinal co-occurrence patterns of ACEs across childhood and adolescence, and self-harm and depression in adolescence and early adulthood. We included 8,859 young people from the Avon Longitudinal Study of Parents and Children (ALSPAC). We examined ten ACEs reported prospectively and retrospectively by parents and children throughout childhood and adolescence, and retrospectively by cohort members in adulthood. Self-harm and depression were self-reported in adolescence (age 16 years) and early adulthood (ages 23 and 24 years). Logistic regression models examined associations between previously derived latent classes of co-occurring ACEs over time, and self-harm and depression. A higher risk of adolescent self-harm was found for each of the latent classes when compared to the Low ACEs reference class (n = 6,380) (Mid-childhood and adolescence ACEsn = 230; adjusted odds ratio (aOR) 1.76, 95% CI 1.11–2.80; Early childhood abuse and parental mental health problemsn = 445; aOR 1.85, 95% CI 1.34–2.56; Persistent parental mental health problemsn = 861; aOR 1.44, 95% CI 1.07–1.94; Early and mid-childhood household disharmonyn = 943; aOR 1.47, 95% CI 1.10–1.97). The association between Persistent parental mental health problems and self-harm persisted in early adulthood (aOR 1.57, 95% CI 1.16–2.12). For adolescent depression, associations were found with the Early childhood abuse and parental mental health problems (aOR 2.89, 95% CI 2.20–3.79), Persistent parental mental health problems (aOR 1.54, 95% CI 1.18–2.01), and Early and mid-childhood household disharmony (aOR 1.36, 95% CI 1.03–1.81) classes when compared to the Low ACEs class. These associations persisted in early adulthood. Early childhood abuse and parental mental health problems (aOR 2.50, 95% CI 1.68–3.73) and Early and mid-childhood household disharmony (aOR 1.58, 95% CI 1.05–2.37) were associated with a higher likelihood of co-occurring self-harm and depression in adolescence. However by early adulthood, only Persistent parental mental health problems were associated with a higher likelihood of co-occurring self-harm and depression (aOR 2.13, 95% CI 1.47–3.10). ACEs occurring throughout childhood and adolescence are associated with a higher risk of adolescent self-harm and both adolescent and early adulthood depression. In contrast, the class most strongly associated with early adult self-harm was Persistent parental mental health problems. Multicomponent interventions and multi-sectoral preventative efforts are needed to address distinct patterns of co-occurring ACEs during childhood and adolescence, to mitigate their short- and long-term impacts on self-harm and depression.